Microstructure evolution of micellar casein powder upon ageing: Consequences on rehydration dynamics. (August 2017) - Nasser, Sarah; Jeantet, Romain; De-Sa-Peixoto, Paulo; Ronse, Gilles; Nuns, Nicolas; Pourpoint, Frederique; Burgain, Jennifer; Gaiani, Claire; Hédoux, Alain; Delaplace, Guillaume
Abstract: Micellar casein (MC) powder must be completely dispersed and dissolved in water to fully exhibit their functional properties. However, the rehydration properties of these powders decline strongly during storage, leading to loss of solubility and longer rehydration time. In this work, controlled ageing was applied to a MC powder in order to better understand the mechanisms responsible for the deterioration of rehydration properties in the course of storage. The objective was to investigate evolutions of powder surface structure and composition as well as the link between these changes and the decline in rehydration properties, which were evaluated through characteristic times of different steps constituting the full rehydration process. Lipid migration (towards the particle surface) and increase of interactions between surface micellar particles during storage were proven to be responsible for major changes in different rehydration stages. First, the delay in water penetration into particles was quantified; then, the increase of particle fragmentation time was determined and finally, an extended total rehydration time was evidenced. Analysis of the characteristic times of different rehydration stages shows unambiguously that the main step increasing the total rehydration time of aged powder is not lipid migration but the crosslink formation during storage, which can thus be considered as the rate-limiting stage for rehydration of aged powder. Highlights: Increase in the migration of surface lipids, surface crust resistance and rehydration characteristic times were demonstrated. A strong correlation was demonstrated between migration of lipids to the surface and increase of wetting time. It was clearly established that wetting step was not the main reason for extended total rehydration time upon ageing. Delayed casein micelles release is considered as the rate-limiting stage for rehydration of aged powder.